A bamboo-based synthetic inorganic paper and a method for preparing the same
Patent Information
- Application Number
- CN202611256972.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-19
- Publication Date
- 2026-10-27
AI Technical Summary
[0004]本发明的目的在于解决传统石头纸塑料含量高、难降解,以及传统纸怕水、污染大的问题,从而提供一种竹基合成无机纸及其制备方法
完全防水且环保:整体材料以无机矿物和竹纤维为主,塑料用量降至10%左右且为可降解树脂,纸张吸水率极低(<0.1%),废弃后在土壤微生物及酸性环境下可发生崩解,环保价值极高。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of papermaking and environmental protection materials technology, and in particular to a bamboo-based synthetic inorganic paper and its preparation method. Background Technology
[0002] Traditional plant fiber papermaking (wood pulp, straw pulp) consumes large amounts of wood and water, resulting in severe water pollution. The emerging "stone paper" technology, using calcium carbonate and polymer plastics (PE / PP) as raw materials, achieves zero water consumption and waterproofing, but because it contains 20%-30% petroleum-based non-degradable plastics, it easily causes "white pollution" after disposal, contradicting the current global trend of limiting plastics and reducing carbon emissions. Furthermore, the tensile strength of traditional stone paper relies entirely on plastic, lacking the flexibility of natural fibers.
[0003] Bamboo has a short growth cycle, high cellulose content, and long fibers, making it an excellent natural reinforcing material. If bamboo fiber could replace the plastic tensile mesh in traditional stone paper, it would reduce the amount of plastic used while maintaining the paper's water resistance and high tensile strength. However, there is currently a lack of relevant technology to effectively combine bamboo fiber with a large amount of inorganic powder for molding. Summary of the Invention
[0004] The purpose of this invention is to solve the problems of high plastic content and difficulty in degradation of traditional stone paper, as well as the problems of traditional paper being susceptible to water and causing significant pollution, thereby providing a bamboo-based synthetic inorganic paper and its preparation method.
[0005] To achieve the above-mentioned objectives, the present invention provides the following technical solution: This invention provides a bamboo-based synthetic inorganic paper, prepared from raw materials comprising the following parts by weight: 60-70 parts of hydrophobically modified calcium carbonate, 15-25 parts of bamboo fiber, 5-15 parts of biodegradable resin, and 1-20 parts of additives.
[0006] Preferably, the preparation method of hydrophobically modified calcium carbonate includes the following steps: The hydrophobically modified calcium carbonate is obtained by coating calcium carbonate with a mixture of calcium carbonate, silane coupling agent and stearic acid.
[0007] Preferably, calcium carbonate has a D50 of 2~8 μm; The mass ratio of silane coupling agent to stearic acid is 1~2:1~2; The combined mass of the silane coupling agent and stearic acid is 1-3% of the mass of calcium carbonate; The coating temperature is 80~120℃, and the time is 10~20min.
[0008] Preferably, the beating degree of bamboo fiber is 45~65°SR.
[0009] Preferably, the aspect ratio of bamboo fiber is ≥10.
[0010] Preferably, the biodegradable resin is one or more of polybutylene adipate / terephthalate, polylactic acid, polycaprolactone, and polybutylene succinate. Additives include plasticizers and / or lubricants.
[0011] This invention provides a method for preparing the bamboo-based synthetic inorganic paper, comprising the following steps: (1) Mix the raw materials, melt and granulate them to obtain composite masterbatch; (2) The composite masterbatch is melt-cast and calendered in sequence to obtain the bamboo-based synthetic inorganic paper.
[0012] Preferably, the temperature of the melt casting in step (2) is 150~170℃.
[0013] Preferably, the rolling and shaping temperature in step (2) is 80~110℃.
[0014] Preferably, the rolling line pressure in step (2) is 50~100N / mm.
[0015] This invention provides a bamboo-based synthetic inorganic paper, prepared from raw materials comprising the following parts by weight: 60-70 parts of hydrophobically modified calcium carbonate, 15-25 parts of bamboo fiber, 5-15 parts of biodegradable resin, and 1-20 parts of additives. This synthetic inorganic paper uses ultrafine modified calcium carbonate as the main material, bamboo fiber extracted from raw bamboo and flexibly ground to retain a high aspect ratio as tensile support, and biodegradable resin as a binder. This invention employs high aspect ratio bamboo fiber grinding: the bamboo fiber cannot be excessively pulverized; it needs to be flexibly ground using a disc mill to microfibrilize it, retaining the aspect ratio, so that it forms a dense "three-dimensional network skeleton" in the paper, providing excellent physical tensile strength.
[0016] This invention also provides a method for preparing bamboo-based synthetic inorganic paper. The raw materials are mixed, melted, and granulated to obtain a composite masterbatch. The composite masterbatch is then sequentially melt-cast and calendered to obtain the bamboo-based synthetic inorganic paper. This invention utilizes interfacial coupling and casting molding. The inorganic powder (CaCO3) is hydrophilic, while bamboo fiber contains hydroxyl groups and is hydrophilic; therefore, they cannot be directly hot-pressed. The surface of CaCO3 is modified to be hydrophobic using a silane coupling agent, and a small amount of biodegradable resin is introduced as a binder phase. Under high-temperature casting and calendering, the molten resin encapsulates the modified CaCO3 and penetrates into the bamboo fiber network, forming a dense, waterproof synthetic paper upon cooling.
[0017] The beneficial effects of this invention are as follows: Completely waterproof and environmentally friendly: The overall material is mainly inorganic minerals and bamboo fiber, with plastic content reduced to about 10% and it is made of biodegradable resin. The paper has an extremely low water absorption rate (<0.1%) and can decompose in soil microorganisms and acidic environments after being discarded, making it extremely valuable for environmental protection.
[0018] High strength and high added value: The skeletal support of bamboo fiber makes the paper's tear resistance far exceed that of ordinary stone paper, making it suitable for high-end waterproof packaging, map paper, outdoor advertising paper and other high-value-added applications.
[0019] Zero-water-consumption papermaking: No water is required as a dispersion medium throughout the entire process, completely eliminating water pollution in papermaking.
[0020] This invention utilizes the natural high strength of bamboo fiber to replace the petroleum-based plastic mesh in traditional stone paper. This not only achieves complete waterproofing and excellent writing and printing performance, but also allows the product to partially degrade naturally, significantly reducing carbon emissions. It breaks through the technical bottlenecks of high water consumption and difficult degradation of traditional papermaking, resulting in extremely high added value. Detailed Implementation
[0021] This invention provides a bamboo-based synthetic inorganic paper, prepared from raw materials comprising the following parts by weight: 60-70 parts of hydrophobically modified calcium carbonate, 15-25 parts of bamboo fiber, 5-15 parts of biodegradable resin, and 1-20 parts of additives.
[0022] In this invention, the mass fraction of hydrophobically modified calcium carbonate is preferably 61 to 69 parts, more preferably 62 to 68 parts, and even more preferably 64 to 66 parts.
[0023] In this invention, the preferred mass fraction of bamboo fiber is 16 to 24 parts, more preferably 18 to 22 parts, and even more preferably 19 to 20 parts.
[0024] In this invention, the biodegradable resin is preferably 6 to 14 parts by mass, more preferably 7 to 13 parts, and even more preferably 8 to 12 parts by mass.
[0025] In this invention, the mass fraction of the additive is preferably 2 to 18 parts, more preferably 5 to 15 parts, and even more preferably 8 to 12 parts.
[0026] In this invention, the preparation method of hydrophobically modified calcium carbonate includes the following steps: The hydrophobically modified calcium carbonate is obtained by coating calcium carbonate with a mixture of calcium carbonate, silane coupling agent and stearic acid.
[0027] In this invention, the D50 of calcium carbonate is preferably 2~8μm, more preferably 3~7μm, and even more preferably 4~6μm.
[0028] In this invention, the mass ratio of silane coupling agent to stearic acid is preferably 1~2:1~2, more preferably 1.2~1.8:1.2~1.8, and even more preferably 1.4~1.6:1.4~1.6.
[0029] In this invention, the mass of the silane coupling agent and stearic acid is preferably 1 to 3% of the mass of calcium carbonate, more preferably 1.5 to 2.5%, and even more preferably 1.8 to 2.2%.
[0030] In this invention, the coating temperature is preferably 80~120℃, more preferably 90~110℃, and even more preferably 95~105℃; the coating time is preferably 10~20min, more preferably 12~18min, and even more preferably 14~16min; the purpose of coating is to perform hydrophobic modification.
[0031] In this invention, raw bamboo is sequentially subjected to mechanical combing and wet flexible grinding, and then dehydrated and dried to obtain bamboo fiber.
[0032] In this invention, wet flexible grinding is performed using a disc mill or a pulping machine.
[0033] In this invention, after wet flexible milling, the beating degree of bamboo fiber is preferably 45~65°SR, more preferably 50~60°SR, and even more preferably 54~56°SR.
[0034] In this invention, the aspect ratio of bamboo fiber is preferably ≥10, more preferably ≥15, and even more preferably ≥20; microfiberization is achieved and a high aspect ratio structure is maintained through wet flexible milling.
[0035] In this invention, the biodegradable resin is one or more of polybutylene adipate / terephthalate (PBAT), polylactic acid (PLA), polycaprolactone (PCL), and polybutylene succinate (PBS).
[0036] In this invention, the additives include plasticizers and / or lubricants.
[0037] In this invention, the plasticizer is one or more of epoxidized soybean oil, acetylated tributyl citrate (ATBC), tributyl citrate (TBC), polyethylene glycol 4000 (PEG4000), and dibutyl sebacate (DBS).
[0038] In this invention, the lubricant is one or more of stearic acid, calcium stearate, zinc stearate, erucamide, oleamide, and ethylene bis-stearamide (EBS).
[0039] This invention also provides a method for preparing the bamboo-based synthetic inorganic paper, comprising the following steps: (1) Mix the raw materials, melt and granulate them to obtain composite masterbatch; (2) The composite masterbatch is melt-cast and calendered in sequence to obtain the bamboo-based synthetic inorganic paper.
[0040] In this invention, the die head for melt casting in step (2) is a T-shaped die head, and the melt casting temperature is preferably 150~170℃, more preferably 155~165℃, and even more preferably 158~162℃.
[0041] In this invention, the molten cast melt is fed to a cooling roller for preliminary cooling. The temperature for preliminary cooling and shaping is preferably 20~40°C, more preferably 25~35°C, and even more preferably 28~32°C. After preliminary cooling and shaping, the next step of calendering and shaping is carried out.
[0042] In this invention, the calendering temperature in step (2) is preferably 80~110℃, more preferably 90~100℃, and even more preferably 95~98℃.
[0043] In this invention, the rolling line pressure in step (2) is preferably 50~100N / mm, more preferably 60~90N / mm, and even more preferably 70~80N / mm.
[0044] In this invention, after calendering and setting, stretching, cooling, trimming, and winding are performed sequentially to obtain bamboo-based synthetic inorganic paper.
[0045] The bamboo-based synthetic inorganic paper provided by this invention has a water absorption rate of <0.1%, a longitudinal tensile strength of >25 MPa, a tear strength of >300 mN, and a mass degradation rate of ≥40% under natural composting conditions for 180 days.
[0046] The technical solutions provided by the present invention will be described in detail below with reference to the embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0047] Example 1
[0048] Bamboo fiber preparation: 3-year-old bamboo was taken, mechanically de-noded and loosened, and wet-grinded in a disc mill for 5 hours. The pulping degree was 55°SR. After dehydration and drying, the average length-to-diameter ratio of the fiber was measured to be 15.
[0049] Calcium carbonate modification: Take heavy calcium carbonate and air-mill it to D50=3μm. Add 1.2% by weight of silane coupling agent KH-560 and 1% stearic acid. Modify it in a high-speed kneader at 100℃ for 15 minutes.
[0050] Mixing and granulation: Mix the following materials according to the following mass ratio: 65 parts modified calcium carbonate, 22 parts bamboo fiber, 12 parts PBAT resin, and 1 part epoxidized soybean oil (plasticizer), and granulate them using a twin-screw extruder.
[0051] Casting and calendering: The masterbatch is melted at 160℃ through an extruder, extruded through a T-die, shaped by a cooling roller (30℃), then compacted and calendered by a four-roll calender (90℃, 75N / mm), and finally cooled and wound to obtain bamboo-based synthetic inorganic paper with a thickness of 120μm.
[0052] Performance testing: The performance of the bamboo-based inorganic paper prepared in Example 1 was tested and compared with that of commercially available traditional stone paper (PE-based). The test results are recorded in Table 1: Water absorption test: After immersion in water for 24 hours, the water absorption rate of the paper in Example 1 was 0.05%, and water droplets on the surface rolled off as beads, indicating that it was completely waterproof.
[0053] Mechanical properties: longitudinal tensile strength 28 MPa (commercially available stone paper is about 20 MPa), tear strength 350 mN (superior to commercially available), proving that the bamboo fiber skeleton plays an excellent role in tensile support.
[0054] Degradation test: Under natural composting conditions for 180 days, the sample mass loss rate of Example 1 reached more than 45% (bamboo fiber and PBAT degraded, and calcium carbonate returned to nature), while traditional stone paper showed no significant change.
[0055] Table 1. Performance test results of bamboo-based synthetic inorganic paper in Example 1
[0056] As can be seen from Example 1, the present invention successfully combines the high-value utilization of bamboo with inorganic minerals, and the resulting synthetic paper not only has excellent performance, but also has great commercial promotion value in the market of interior packaging and high-end waterproof printing products in the context of automotive lightweighting.
[0057] Example 2 (PLA-based system - high stiffness and high whiteness)
[0058] Bamboo fiber preparation: Four-year-old moso bamboo was mechanically de-noded and loosened, and then wet-milled in a disc mill for 4 hours. The pulping degree was 50°SR. After dehydration and drying, the average length-to-diameter ratio of the fiber was measured to be 20.
[0059] Calcium carbonate modification: Take heavy calcium carbonate and air-mill it to D50=5μm. Add 1.5% by weight of silane coupling agent KH-550 and 1.5% stearic acid. Modify it in a high-speed kneader at 110℃ for 12 minutes.
[0060] Mixing and granulation: Mix the following materials according to the following mass ratios: 68 parts modified calcium carbonate, 18 parts bamboo fiber, 8 parts PLA resin, 2 parts ATBC (plasticizer), and 2 parts calcium stearate (lubricant), and granulate them using a twin-screw extruder.
[0061] Casting and calendering: The masterbatch is melted at 158℃ through an extruder, extruded through a T-die, shaped by a cooling roller (28℃), then compacted and calendered by a four-roll calender (95℃, 70N / mm), and finally cooled and wound to obtain bamboo-based synthetic inorganic paper with a thickness of 110μm. The performance test results are recorded in Table 2.
[0062] Table 2. Performance test results of bamboo-based synthetic inorganic paper in Example 2
[0063] Analysis: PLA resin has greater rigidity, resulting in better paper stiffness and whiteness compared to the PBAT system, but its tear resistance is slightly reduced due to the resin's brittleness; its degradation rate is lower than that of the PBAT system because PLA degrades relatively slowly under natural composting conditions.
[0064] Example 3 (PBAT+PLA compound system – optimal overall performance)
[0065] Bamboo fiber preparation: 3-year-old bamboo was taken, mechanically de-noded and loosened, and wet-grinded in a disc mill for 5.5 hours. The beating degree was 58°SR. After dehydration and drying, the average length-to-diameter ratio of the fiber was measured to be 18.
[0066] Calcium carbonate modification: Take heavy calcium carbonate and air-mill it to D50=4μm. Add 1.8% by weight of silane coupling agent KH-560 and 1.2% stearic acid. Modify it in a high-speed kneader at 105℃ for 16 minutes.
[0067] Mixing and granulation: Mix the following materials according to the following mass ratios: 62 parts modified calcium carbonate, 20 parts bamboo fiber, 5 parts PBAT resin, 5 parts PLA resin, 3 parts epoxidized soybean oil (plasticizer), and 1 part erucamide (lubricant), and granulate them using a twin-screw extruder.
[0068] Casting and calendering: The masterbatch is melted at 162℃ through an extruder, extruded through a T-die, shaped by a cooling roller (30℃), compacted and calendered by a four-roll calender (92℃, 75N / mm), and finally cooled and wound to obtain bamboo-based synthetic inorganic paper with a thickness of 115μm. The performance test results are recorded in Table 3.
[0069] Table 3. Performance test results of bamboo-based synthetic inorganic paper in Example 3
[0070] Analysis: PBAT and PLA are blended in a 1:1 ratio. PBAT provides flexibility and extensibility, while PLA provides rigidity and strength. The synergy between the two results in optimal overall mechanical properties of the paper. The bamboo fiber content is moderate (20 parts), with an aspect ratio of 18, forming a good three-dimensional network framework.
[0071] Example 4 (PCL-based system - ultra-flexible and suitable for low temperature)
[0072] Bamboo fiber preparation: 5-year-old hard-headed yellow bamboo was taken, mechanically de-noded and loosened, and wet-grinded in a disc mill for 3 hours. The pulping degree was 45°SR. After dehydration and drying, the average length-to-diameter ratio of the fiber was measured to be 12.
[0073] Calcium carbonate modification: Take heavy calcium carbonate and air-mill it to D50=6μm. Add 2% by weight of silane coupling agent KH-570 and 1% stearic acid. Modify it in a high-speed kneader at 95℃ for 18 minutes.
[0074] Mixing and granulation: Mix the following materials according to the following mass ratios: 70 parts modified calcium carbonate, 15 parts bamboo fiber, 10 parts PCL resin, 1 part PEG4000 (plasticizer), and 2 parts zinc stearate (lubricant), and granulate them using a twin-screw extruder.
[0075] Casting and calendering: The masterbatch is melted at 155℃ through an extruder, extruded through a T-die, shaped by a cooling roller (25℃), compacted and calendered by a four-roll calender (88℃, 65N / mm), and finally cooled and wound to obtain bamboo-based synthetic inorganic paper with a thickness of 105μm. The performance test results are recorded in Table 4.
[0076] Table 4. Performance test results of bamboo-based synthetic inorganic paper in Example 4
[0077] Analysis: PCL has a low melting point (approximately 60°C) and a low glass transition temperature (approximately -60°C), giving paper excellent low-temperature flexibility, with folding endurance far exceeding other systems at -20°C. However, PCL has high crystallinity, resulting in relatively weak interfacial bonding with calcium carbonate, leading to lower strength at room temperature.
[0078] Example 5 (PBS-based system - high strength and high degradation)
[0079] Bamboo fiber preparation: Two-year-old green bamboo was taken, mechanically de-noded and loosened, and wet-grinded in a disc mill for 6 hours. The pulping degree was 65°SR. After dehydration and drying, the average length-to-diameter ratio of the fiber was measured to be 25.
[0080] Calcium carbonate modification: Take heavy calcium carbonate and air-mill it to D50=2μm. Add 1% by weight of silane coupling agent KH-560 and 0.8% stearic acid, and modify it in a high-speed kneader at 90℃ for 20 minutes.
[0081] Mixing and granulation: Mix 60 parts modified calcium carbonate, 25 parts bamboo fiber, 8 parts PBS resin, 3 parts tributyl citrate (plasticizer), and 2 parts oleamide (lubricant) by mass ratio, and granulate by twin-screw extruder.
[0082] Casting and calendering: The masterbatch is melted at 165℃ through an extruder, extruded through a T-die, shaped by a cooling roller (32℃), compacted and calendered by a four-roll calender (98℃, 80N / mm), and finally cooled and wound to obtain bamboo-based synthetic inorganic paper with a thickness of 125μm. The performance test results are recorded in Table 5.
[0083] Table 5. Performance test results of bamboo-based synthetic inorganic paper in Example 5
[0084] Analysis: This example exhibits the highest bamboo fiber content (25 parts), the largest aspect ratio (25), and the finest calcium carbonate particle size (D50=2μm). The bamboo fiber three-dimensional network skeleton is also the densest, resulting in the best overall mechanical properties. PBS degrades better than PBAT, and due to the high bamboo fiber content, the degradation rate reaches a maximum of 52%. However, the water absorption rate is slightly higher because of the high bamboo fiber content and high freeness (65°SR), resulting in more exposed hydrophilic groups in the fibers.
[0085] Example 6 (Optimized Formulation – Industrial Recommendation)
[0086] Bamboo fiber preparation: 3-year-old bamboo and 4-year-old bamboo were mixed in a 1:1 ratio, mechanically removed nodes and loosened, and then wet-milled in a disc mill for 4.5 hours. The pulping degree was 52°SR. After dehydration and drying, the average length-to-diameter ratio of the fiber was measured to be 22.
[0087] Calcium carbonate modification: Take heavy calcium carbonate and air-mill it to D50=4μm. Add 1.6% by weight of silane coupling agent KH-560 and 1.4% stearic acid. Modify it in a high-speed kneader at 100℃ for 15 minutes.
[0088] Mixing and granulation: Mix the following materials according to the following mass ratios: 66 parts modified calcium carbonate, 19 parts bamboo fiber, 7 parts PBAT resin, 3 parts PLA resin, 2 parts ATBC (plasticizer), 1 part stearic acid (lubricant), and 1 part erucamide (lubricant), and granulate them using a twin-screw extruder.
[0089] Casting and calendering: The masterbatch is melted at 160℃ through an extruder, extruded through a T-die, shaped by a cooling roller (30℃), compacted and calendered by a four-roll calender (95℃, 75N / mm), and finally stretched longitudinally (stretch ratio 1.15), cooled, trimmed, and wound to obtain bamboo-based synthetic inorganic paper with a thickness of 118μm. The performance test results are recorded in Table 6.
[0090] Table 6. Performance test results of bamboo-based synthetic inorganic paper in Example 6
[0091] Analysis: This embodiment features a comprehensively optimized formulation. The PBAT:PLA ratio of 7:3 balances flexibility and rigidity, while the bamboo fiber aspect ratio of 22 achieves a balance between strength and processability. ATBC provides high plasticizing efficiency and is environmentally friendly, and the combination of stearic acid and erucamide provides synergistic internal and external lubrication. After longitudinal stretching, the fiber orientation along the longitudinal direction is improved, further enhancing longitudinal strength. Carbon emissions are only about 45% of those of traditional stone paper.
[0092] Comparative Example 1 (Unmodified calcium carbonate)
[0093] Preparation method: Same as in Example 1, but the calcium carbonate was not hydrophobically modified (no silane coupling agent and stearic acid were added), and heavy calcium carbonate with D50=3μm was used directly. The performance test results are recorded in Table 7.
[0094] Table 7. Paper performance test results for Comparative Example 1
[0095] Analysis: Unmodified calcium carbonate has a hydrophilic surface and poor compatibility with hydrophobic PBAT resin, resulting in uneven dispersion, weak interfacial bonding, a sharp increase in paper water absorption, and a significant decrease in strength, which fully demonstrates the necessity of hydrophobic modification.
[0096] Comparative Example 2 (over-crushed bamboo fiber)
[0097] Preparation method: Same as in Example 1, but the bamboo fiber was ground in a disc mill for 8 hours, the beating degree was 78°SR, and the average aspect ratio of the fiber was reduced to 6. The performance test results are recorded in Table 8.
[0098] Table 8. Paper performance test results for Comparative Example 2
[0099] Analysis: Excessive grinding leads to a severe reduction in the aspect ratio of bamboo fibers, making it impossible to form an effective three-dimensional network skeleton and significantly weakening the tensile support. This proves that the core technology of "flexible grinding to retain a high aspect ratio" in this invention is crucial.
[0100] Through comparison of the above embodiments, the inventiveness of the present invention is reflected in the following dimensions: 1. Component synergistic effect: Examples 3 and 6 demonstrate that the combination of PBAT and PLA is superior to that of a single resin, with complementary flexibility and rigidity; 2. The key role of the aspect ratio of bamboo fiber: Example 5 (L / D=25) vs Comparative Example 2 (L / D=6), the tear strength differs by 2.5 times; 3. The necessity of hydrophobic modification: Example 1 vs. Comparative Example 1, the water absorption rate differs by 37 times; 4. Window effect of beating degree: Within the range of 45~65°SR, 52~58°SR is the optimal range (Examples 3 and 6). Too high (78°SR, Comparative Example 2) or too low (45°SR, Example 4) are not conducive to the overall performance. 5. Balance of calcium carbonate particle size: D50 = 2~5μm is the preferred range. Too coarse (6μm, Example 4) leads to a decrease in strength, while too fine increases the cost. 6. Balance between degradation rate and strength: Example 5 has the highest degradation rate (52%) but slightly higher water absorption rate, while Example 6 achieves the best balance between degradation rate (48%) and overall performance.
[0101] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A bamboo-based synthetic inorganic paper, characterized in that, It is prepared from raw materials comprising the following parts by mass: 60-70 parts of hydrophobically modified calcium carbonate, 15-25 parts of bamboo fiber, 5-15 parts of biodegradable resin, and 1-20 parts of additives.
2. The bamboo-based synthetic inorganic paper as described in claim 1, characterized in that, The preparation method of hydrophobically modified calcium carbonate includes the following steps: The hydrophobically modified calcium carbonate is obtained by coating calcium carbonate with a mixture of calcium carbonate, silane coupling agent and stearic acid.
3. The bamboo-based synthetic inorganic paper as described in claim 2, characterized in that, The D50 of calcium carbonate is 2~8 μm; The mass ratio of silane coupling agent to stearic acid is 1~2:1~2; The combined mass of the silane coupling agent and stearic acid is 1-3% of the mass of calcium carbonate; The coating temperature is 80~120℃, and the time is 10~20min.
4. The bamboo-based synthetic inorganic paper as described in claim 3, characterized in that, The beating degree of bamboo fiber is 45~65°SR.
5. The bamboo-based synthetic inorganic paper as described in claim 4, characterized in that, Bamboo fiber has an aspect ratio ≥10.
6. The bamboo-based synthetic inorganic paper as described in claim 5, characterized in that, The biodegradable resin is one or more of polybutylene adipate / terephthalate, polylactic acid, polycaprolactone, and polybutylene succinate; Additives include plasticizers and / or lubricants.
7. The method for preparing bamboo-based synthetic inorganic paper according to any one of claims 1 to 6, characterized in that, Includes the following steps: (1) Mix the raw materials, melt and granulate them to obtain composite masterbatch; (2) The composite masterbatch is melt-cast and calendered in sequence to obtain the bamboo-based synthetic inorganic paper.
8. The method for preparing bamboo-based synthetic inorganic paper as described in claim 7, characterized in that, The temperature of melt casting in step (2) is 150~170℃.
9. The method for preparing bamboo-based synthetic inorganic paper as described in claim 8, characterized in that, The calendering and setting temperature in step (2) is 80~110℃.
10. The method for preparing bamboo-based synthetic inorganic paper as described in claim 9, characterized in that, In step (2), the rolling line pressure is 50~100N / mm.